Study of heat transfer by thermal expansion of connate water ahead of a steam chamber edge in the steam-assisted-gravity-drainage process. (15th June 2015) - Ji, Dongqi; Zhong, He; Dong, Mingzhe; Chen, Zhangxin
Highlights: Proposed a modeling of heat transfer by thermal expansion in SAGD. Proved the important convection heat transfer ahead a steam chamber in SAGD. Provided heat efficiency improvement methods in SAGD. Abstract: Steam-Assisted Gravity Drainage (SAGD) has been the preferred thermal method for bitumen recovery from reservoirs in western Canada, such as Athabasca and Cold Lake. In SAGD, near the edge of a steam chamber, the viscosity of bitumen can be reduced by several orders of magnitude by the release of latent heat from injected steam. Consequently, the heated bitumen flows downwards to a horizontal production well, under the action of gravity. A critical control of oil production performance in SAGD is the heat transfer ahead of the steam chamber edge. It is commonly suggested that heat conduction is the only, or dominant, mechanism for heat to be transferred to the cold oil sands. Heat transfer through convection is neglected in classical models, such as in Butler's theory. Although a few mathematical studies have recently been performed to examine the role of convective heat transfer through condensate flow perpendicular or parallel to the steam chamber edge, the role of heat transfer by cold connate water thermal expansion in SAGD has been given little attention. In this study, an analytical model is derived for heat transfer induced by thermal expansion of the connate water, and the result is reasonably consistent with the numerical simulation results obtained by running CMG STARS. The relative roles of conduction and convection ahead of the steam chamber edge are re-examined. The results show that heat convection accounts for a much higher percentage of the total heat transfer than conduction. This study also suggests that parameters that have a close relationship with the thermal expansion of connate water, such as the steam injection temperature and connate water saturation, can affect the relative roles of conductive and convective heat transfer in SAGD. Based on this study, the heat transfer efficiency can be enhanced through improving convection induced by thermal expansion of connate water.